2016
DOI: 10.1016/j.scitotenv.2016.02.024
|View full text |Cite
|
Sign up to set email alerts
|

Redundancy in the ecological assessment of lakes: Are phytoplankton, macrophytes and phytobenthos all necessary?

Abstract: Although the Water Framework Directive specifies that macrophytes and phytobenthos should be used for the ecological assessment of lakes and rivers, practice varies widely throughout the EU. Most countries have separate methods for macrophytes and phytobenthos in rivers; however, the situation is very different for lakes. Here, 16 countries do not have dedicated phytobenthos methods, some include filamentous algae within macrophyte survey methods whilst others use diatoms as proxies for phytobenthos. The most … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
32
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 42 publications
(33 citation statements)
references
References 32 publications
0
32
0
1
Order By: Relevance
“…In practice, this would mean either a weak or no correlation between biological metrics and pressure gradient. However, diatom-based metrics generally show a highly significant and strong response to nutrient gradients (Kelly et al, , 2016a with correlation coefficients similar to or better than those shown by other biological elements (Birk et al, 2012). This, therefore, is not good grounds for excluding phytobenthos.…”
Section: Phytobenthos For Ecological Assessment Of Lakesmentioning
confidence: 91%
See 3 more Smart Citations
“…In practice, this would mean either a weak or no correlation between biological metrics and pressure gradient. However, diatom-based metrics generally show a highly significant and strong response to nutrient gradients (Kelly et al, , 2016a with correlation coefficients similar to or better than those shown by other biological elements (Birk et al, 2012). This, therefore, is not good grounds for excluding phytobenthos.…”
Section: Phytobenthos For Ecological Assessment Of Lakesmentioning
confidence: 91%
“…This, therefore, is not good grounds for excluding phytobenthos. Instead, the main reason stated by Member States is redundancy, noting that phytoplankton and macrophytes already address eutrophication pressure (Kelly et al, 2016a).…”
Section: Phytobenthos For Ecological Assessment Of Lakesmentioning
confidence: 99%
See 2 more Smart Citations
“…For each BQE, the value of a quality index should be compared to a reference value indicating minimal human impact to obtain an ecological quality ratio. Macrophytes and phytobenthos are components of freshwater flora and are included by Annex 5 of the WFD in a single BQE, but they are evaluated separately, as they can respond differently to human impact, in relation to site-specific conditions (Schneider et al, 2012;Kelly et al, 2016).…”
Section: Introductionmentioning
confidence: 99%